Design and analysis of large lithium-Ion battery systems - Santhanagopalan, Shriram; Kim, Gi-Heon; Keyers, Matthew; Pesaran, Ahmad A.; Smith, Kandler; Neubauer, Jeremy (Artech House power engineering series., 2015)
This new resource provides you with an introduction to battery design and test considerations for large-scale automotive, aerospace, and grid applications. It details the logistics of designing a professional, large, Lithium-ion battery pack, primarily for the automotive industry, but also for non-automotive applications. Topics such as thermal management for such high-energy and high-power units are covered extensively, including detailed design examples. Every aspect of battery design and analysis is presented from a hands-on perspective. The authors work extensively with engineers in the fie.